French denumerals in -aire. (March 2019) - Fradin, Bernard
Abstract : This article investigates French nouns and adjectives in - aire related to numerals. The original series was borrowed from Latin distributive numerals and its elements exhibited various meanings. Some of them still exist with their original meaning but have a vestigial use. Grammars and linguistic studies barely mention these forms and completely overlook the fact that new series of forms with a meaning referring to age or an anniversary have recently developed. The present article documents this development and the reasons behind it. It also addresses the issues tied to the variations of form and meaning that the patterns in question exhibit.